NiTiBOND an optimized self-crimping stapes prosthesis for treatment of otosclerosis - Huber, A. M.; Hornung, Joachim; Plontke, S.; Roeoesli, C.; Iro, Heinrich; Strutz, J.; Rahne, T.; Pezier, T. F.; Kwok, P. (Laryngo-Rhino-Otologie, 2014)
Compared to traditional stapes prostheses, self-crimping prostheses have been shown to result in similar, if not better, closure of the air bone gap in patients undergoing stapedotomy for otosclerosis. To achieve self-crimping, nitinol, a shape memory alloy, has been used for several years but concerns have been raised regarding possible damage to the incus and its muco-periosteum. We investigate these concerns with regard to the newer NiTiBOND stapes prosthesis in an observational multi-centre study.In a multicentre, prospective observational study, 76 patients undergoing stapedotomy with the NiTiBond prosthesis across 4 centres were compared to 75 -retrospectively selected control SMart patients. Complications, intra-operative user-friendliness and audiological results at 3 months were documented.Audiological improvement and the rate of complications were similar in both groups. Non inferiority was shown at all frequencies and in the pure-tone average. The NiTiBOND prosthesis was described as very user-friendly.By eliminating manual crimping, stapedotomy using the NiTiBOND prosthesis can be facilitated and standardized. Furthermore, intraoperative handling characteristics of the prosthesis are very good which may further reduce operative risk. Importantly, we show that these benefits are not to the detriment of audiological outcome. Larger and longer-term studies are required to further evaluate results.
EVALuna2:19925